Serum Periostin Predicts Wheezing Exacerbation: A Prospective Study in Preschool Children with Recurrent Wheezing - Pailin Yooma (2022)
Introduction: Wheezing is a common problem in preschool children. Currently, there are no reliable biomarkers that can predict subsequent wheezing in preschool children. This study aimed to compare serum periostin levels between preschool children with and without recurrent wheezing and investigate its utility for predicting acute wheezing exacerbation. Methods: Children aged 2-5 years with recurrent wheezing and healthy control children were enrolled. They were evaluated for serum periostin level at enrollment and subsequently followed for wheezing episodes in a 1-year prospective study. Results: A total of 122 children were enrolled. Children in the recurrent wheezing group (n = 80) had a greater median serum periostin level (1,122.32 pg/mL [<10-6,978.93]) than that of the healthy control group (n = 40) (<10 pg/mL [<10-2,116.69]), p value = 0.006. After 1-year follow-up, subjects who experienced subsequent wheezing exacerbation episodes had a greater median of periostin level (5,321 pg/mL) compared with those with no exacerbation (<10 pg/mL), p value = 0.014. ROC curve analysis revealed that the level of serum periostin >1,200 pg/mL, corresponding to 78.9% sensitivity and 64.6% specificity, with an AUC of 0.701, p value = 0.009, could be a predictor for acute wheezing exacerbation within 1 year. Besides, subjects with serum periostin >1,200 pg/mL had greater odds of subsequent wheezing episodes compared with those with lower levels of serum periostin (adjusted odds ratio 10.0, 95% confidence interval: 2.3-43.5). Conclusions: Preschool children with recurrent wheezing have a greater serum periostin level than healthy control. Serum periostin may be a valuable biomarker for predicting acute wheezing exacerbations in the following year.